Changing the Narrative Language of Prosperity in Africa: A Pentecostal Hermeneutical Challenge - Nel, Marius (Journal for the Study of Religion, 2021)
Pentecostals' central theme in proclamation and practice since the beginning of their movement is holistic healing and wellbeing, resulting from what they term the "Full Gospel". At first, it did not include a prosperous lifestyle. However, a new emphasis on prosperity since the 1980s characterized a part of the African independent church movement with affinities to Pentecostal worship practices, designated as the Neo-Pentecostal movement. The research question for this article is why the narrative language of prosperity within the Pentecostal context changed in Africa and how the damages that it caused can be reversed, and the answer is found in hermeneutical challenges and solutions.
free